2004
DOI: 10.1111/j.1365-2486.2004.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent low temperatures constrain spring recovery of photosynthesis in boreal Scots pine forests

Abstract: During winter and early spring, evergreen boreal conifers are severely stressed because light energy cannot be used when photosynthesis is pre-empted by low ambient temperatures. To study photosynthetic performance dynamics in a severe boreal climate, seasonal changes in photosynthetic pigments, chloroplast proteins and photochemical efficiency were studied in a Scots pine forest near Zotino, Central Siberia. In winter, downregulation of photosynthesis involved loss of chlorophylls, a twofold increase in xanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
246
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(268 citation statements)
references
References 58 publications
19
246
3
Order By: Relevance
“…The needle metabolism also has a clear annual cycle that alternates between the cold tolerance and very low metabolic activity during winter and the strong metabolism and cold vulnerability in summer. The annual cycle is particularly strong in photosynthesis (Ens- G G G G G G G G G G G G G G G G G G G G G G , 2004b;Kolari et al, 2014;Öquist and Huner, 2003;Pelkonen and Hari, 1980). We have worked decades with the annual cycle of vegetation from the analysis of daily shoot elongation (Hari and Leikola, 1972;Hari et al, 1977), bud burst of trees (Hari and Häkkinen, 1991) and photosynthesis (Pelkonen and Hari, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The needle metabolism also has a clear annual cycle that alternates between the cold tolerance and very low metabolic activity during winter and the strong metabolism and cold vulnerability in summer. The annual cycle is particularly strong in photosynthesis (Ens- G G G G G G G G G G G G G G G G G G G G G G , 2004b;Kolari et al, 2014;Öquist and Huner, 2003;Pelkonen and Hari, 1980). We have worked decades with the annual cycle of vegetation from the analysis of daily shoot elongation (Hari and Leikola, 1972;Hari et al, 1977), bud burst of trees (Hari and Häkkinen, 1991) and photosynthesis (Pelkonen and Hari, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…This seasonality has been closely connected to variations in ambient temperatures (Mäkelä et al, 2004;Pelkonen and Hari, 1980) and photoperiod or light intensity changes (Ensminger et al, 2004a;Porcar-Castell et al, 2008). A delayed effect of temperature on photosynthesis recovery in spring is introduced (Mäkelä et al, 2004;Pelkonen and Hari, 1980) and tested with field measurements (Kolari et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there are reports that under certain conditions (e.g. high-light) there is a differential expression of LHCI genes (Bailey et al, 2001;Ensminger et al, 2004;Gáspár et al, 2006). On the other hand, Wehner et al (2004) suggested that the zeaxanthin formed in LHCI proteins is involved in an antioxidative mechanism implicated in suppression of ROS-triggered lipid peroxidation rather than heat energy dissipation (NPQ), which could be consistent with our observations on the accumulation of zeaxanthin ( Figure 3B) which can function as antioxidant, as evidenced by the amount of peroxidized lipids (Figure 4) and the invariable value of NPQ ( Figure 2C).…”
Section: Expression Of Psbs Andmentioning
confidence: 99%
“…from a state of efficient light harvesting to a state of high thermal energy dissipation; Nelson and Yocum, 2006). This change is related to differential expression of genes encoding LHC proteins (Demmig-Adams et al, 1996;Savitch et al, 2002;Ensminger et al, 2004). It was proposed that PsbS, a distant member of the LHC family, might play a protective role within the thylakoids under photoinhibitory conditions, with a central role in NPQ (Li et al, 2000).…”
mentioning
confidence: 99%